1995
DOI: 10.1128/jcm.33.6.1467-1470.1995
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four DNA-based methods for strain delineation of Candida lusitaniae

Abstract: Four methods for the accurate delineation of epidemiologically related and unrelated strains of Candida lusitaniae were compared. Three pulsed-field electrophoretic methods, including two contour-clamped homogeneous field gel electrophoresis methods (EKP-1 and EKP-2) yielding electrophoretic karyotype patterns of intact chromosomal DNA and a method in which the chromosomal DNA was macrodigested with the endonuclease SfiI prior to pulsed-field electrophoresis (MDP), and a random amplified polymorphic DNA (RAPD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 15 publications
(13 reference statements)
0
19
0
1
Order By: Relevance
“…Some authors used the primer with highest discriminative power, 21,30 while others used more than one primer and combined the results for analysis. 11,22,[32][33][34][35] We preferred this latter method, using several primers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors used the primer with highest discriminative power, 21,30 while others used more than one primer and combined the results for analysis. 11,22,[32][33][34][35] We preferred this latter method, using several primers.…”
Section: Discussionmentioning
confidence: 99%
“…12,24 As the use of genotypical methods has increased in recent years, exogenous nosocomial infections have also begun to attract attention, but are still less prevalent than endogenous infections. 23,[30][31][32][33][34][35][36] There are numerous studies investigating the genetic diversity of Candida isolates recovered from ICU patients, and the results about the clonal relationship of the isolates have been varied. Marco et al 23 found crosscontamination between C. albicans isolates recovered from blood cultures of ICU patients, and Arif et al 36 also reported cross-contamination between C. glabrata isolates of ICU patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies used purified DNA as template for PCR typing of Candida species (4, 11,19,23,35,39,42,43,45). Our use of yeast cell lysate makes the PCR protocol easy and fast to perform.…”
Section: Discussionmentioning
confidence: 99%
“…PCR seems to be a promising technique for yeast genotyping. However, since previous PCR studies have been performed using purified yeast DNA as template, the PCR-based genotyping methods applied so far are still relatively laborious (4,11,19,23,35,36,39,42,43,45). PCR performed using crude yeast cell lysates would greatly facilitate the yeast genotyping procedure.…”
mentioning
confidence: 99%
“…In another inter-laboratory study, EK was used effectively to compare strains of C. albicans, C. lusitaniae, C. parapsilosis, C. tropicalis, and C. glabrata [49]. Additionally, this technique has been used to biotype C. parapsilosis, C. dubliniensis, C. lusitaniae, and C. neoformans, by several groups [27,47,[50][51][52][53][54]. However, it cannot be used for epidemiologic investigations of Malassezia spp., since the karyotype of this fungus does not vary intraspecifically [34].…”
Section: E L E C T R O P H O R E T I C K a R Y O T Y P I N G ( E K )mentioning
confidence: 99%